Impact of Macroeconomic Variables on Indian Stock Markets: Examining the Impact of Macroeconomic Variables on the Indian Stock Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study investigates the relationship between the various macroeconomic variables with the Indian stock market. The macroeconomic variables included in the study are interest rate, inflation rate, money supply and exchange rate and BSE Sensex has been taken as the benchmark for the Indian stock market. Monthly data for the period from to has been taken as sample for the study. The study finds that the long term relationship exist between the macroeconomic variables and stock market except the money supply. The short run causality also exist in between the macroeconomic variables and stock market. The bidirectional causality is found in between the interest rate and BSE Sensex.